Learning styles and cognitive achievement: the case of second language learners. - Figueiredo, Sandra (2018)
The learning styles are often associated to the first language development, and neglected in the context of the SL learning. Previous literature states that the kinesthetic learning style is the more appropriated to the language learning, because is the style widely related to youngest learners.